Pengaruh Aplikasi Giberelin (Ga3) Terhadap Perubahan Mutu Fisik Tandan Buah Segar Kelapa Sawit (Elaeis Guineensis Jacq) - Manurung, Saroha; Roosmawati, Febriana; Yosephine, Ingrid Ovie; Kaharuddin, Kaharuddin (UNIVERSITAS LABUHANBATU, 2022)
Physical damage to the fruit affects the quality of Crude Palm Oil (CPO) of palm oil. Gibberellin (GA3) is known as a growth hormone that is able to extend cells and is widely usedin maintaining the shelf life of several types of fruits. This study aims to study the effect of gibberellin dosage, the effect of gibberellin application on the physical quality of oil palm freshfruit bunches. The research was carried out at the North Julok Rayeuk Garden, PT. Perkebunan Nusantara I. The research period was 10 days, in March 2021. This study used a non-factorial Randomized Block Design (RAK) method and 6 replications with a total of 2 samples and a total sample of 48 samples. Parameter testing is compiled on a list of variances and statistical analysis is carried out which tests the average difference with Analysis of Variance (ANOVA) then further tests are carried out using Duncan's Multiple Range Test (DMRT) at 5% level. The results showed that the treatment dose of Gibberellin G1 (15 ml/L water) had a significant effect on reducing fruit loss and had no significant effecton the value of freefatty acids.Â Keywords: Elaeis guineensis Jacq,Gibberellins(GA3),physical quality